Adhoc Election Supervisor's Recruitment Method to Realize Quality Human Resources - Zulkifli Sultan (Formosa Journal of Science and Technology, 2022)
The purpose of this study is to find out the problems in the implementation of the recruitment of ad hoc election supervisors and the right strategy to produce quality human resources for election supervisors. Based on the existing phenomenon that the quality of human resources for election supervisors is still lacking, the public interest is lacking so in the recruitment process sometimes extensions are always carried out even if the number of registrants is lacking. So the process of choosing good human resources is not optimal because there is no choice. This research will use a qualitative approach, namely by collecting data in the field. The data collection technique that will be used is by interviewing 6 informants, direct observations, and analyzing documents collected from data and information starting from the recruitment of the 2015 Regent and Deputy Regent Regional Head Elections (Pilkada). Governor and Deputy Governor 2018 and Election of Regional Heads (Pilkada) of Regents and Deputy Regents 2020. The recruitment of ad hoc election supervisors has undergone several changes and improvements which have increased significantly because socialization and coordination processes have been carried out with local parties in the sub-district area so that the information process is widely open.